1974
DOI: 10.1172/jci107673
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dobutamine on Left Ventricular Performance, Coronary Dynamics, and Distribution of Cardiac Output in Conscious Dogs

Abstract: The effects of dobutamine ([±] ¶4-[2- [[3-(p-hydroxyphenyl itg/kg/min, the drug increased dP/dt/P from 65±3 to 128i4 s' and isolength velocity from 72±4 to 120+7 mm/s without affecting LV end diastolic D significantly. Mean arterial P rose from 92±2 to 104±3 mm Hg and heart rate from 78±3 to 111+7 beats/min, while LV end systolic D fell from 24.1±+1.4 to 19.9±1.8 mm, reflecting a rise in stroke volume from 30±4 to 42±3 ml. Cardiac output rose from 2.41±0.23 to 4.35±0.28 liter/min, while calculated total perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
1
8

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(73 citation statements)
references
References 17 publications
4
60
1
8
Order By: Relevance
“…This finding contrasts with those of the majority of previous studies in which administration of (±)-dobutamine caused no change (Vatner et al, 1974, boluses 1.6-8.Opmol kg-1, infusions 1.6pmol kg-' h-1; Robie & Goldberg, 1975, 0.4-6.4pmol kg-h-1; Leier et al, 1977Leier et al, , 1978.0jumol kg-1 h-1; Liang & Hood, 1979, 2-8pmol kg-1 h-1; Dorszewski et al, 1990, 0.2-0.8zmol kg-1 h-1) or an increase (Ruffolo & Messick, 1985b) in mean arterial blood pressure. However, these differences are likely to be due to differences in administered dose, since Biro .et al.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding contrasts with those of the majority of previous studies in which administration of (±)-dobutamine caused no change (Vatner et al, 1974, boluses 1.6-8.Opmol kg-1, infusions 1.6pmol kg-' h-1; Robie & Goldberg, 1975, 0.4-6.4pmol kg-h-1; Leier et al, 1977Leier et al, , 1978.0jumol kg-1 h-1; Liang & Hood, 1979, 2-8pmol kg-1 h-1; Dorszewski et al, 1990, 0.2-0.8zmol kg-1 h-1) or an increase (Ruffolo & Messick, 1985b) in mean arterial blood pressure. However, these differences are likely to be due to differences in administered dose, since Biro .et al.…”
Section: Discussioncontrasting
confidence: 99%
“…Under the same conditions, mesenteric and renal vascular conductances were either unchanged or, in the case of the latter during the higher dose infusion, reduced. While a relatively selective hindquarters vasodilator effect of (±)-dobutamine has been described previously (Vatner et al, 1974;Robie & Goldberg, 1975;Liang & Hood, 1979) this has not been observed invariably (Drexler et al, 1987;Biro et al, 1988), even in studies that did demonstrate a cerebral vasodilator response to (± )-dobutamine (Drexler et al, 1987). Although there was a greater hindquarters hyperaemia and a better maintenance of mesenteric blood flow during infusion of (+)-dobutamine than of human a-CGRP at either dose level, carotid hyperaemia was greater during infusion of the latter at the higher dose.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…administration of dobutamine to an intact animal produces a lesser increase in systemic blood pressure than that of dopamine (1,2). However, in isolated atria which were perfused with donor's blood, an i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, dobutamine directly increases myocardial contractility without inducing marked tachycardia or greatly changing peripheral arterial resistance in intact dogs (1)(2)(3). In the cat papillary muscle, dobutamine increases the con tractility more but the automaticity less than did isoproterenol (1).…”
mentioning
confidence: 99%